Design and analysis of a high speed double-sided axial flux permanent magnet motor suspended vertically by magnetic bearings - Guney, Omer Faruk; Celik, Ahmet; Bozkurt, Ahmet Fevzi; Erkan, Kadir (IOS PRESS, 2020)
This paper presents the electromagnetic and mechanical analysis of an axial flux permanent magnet (AFPM) motor for high speed (12000 rpm) rotor which is vertically suspended by magnetic bearings. In the analysis, a prototype AFPM motor with a double-sided rotor and a coreless stator between the rotors are considered. Firstly, electromagnetic analysis of the motor is carried out by using magnetic equivalent circuit method. Then, the rotor disk thickness is determined based on a rotor axial displacement due to the attractive force between the permanent magnets placed on opposite rotor disks. Hereafter, an analytical solution is carried out to determine the natural frequencies of the rotor-shaft system. Finally, 3D finite element analysis (FEA) is carried out to verify the analytical results and some experimental results are given to verify the analytical and numerical results and prove the stable high-speed operation.
Keywords: Electromagnetic modeling; high speed; axial flux permanent magnet motor; mechanical stress analysis; rotor vibration analysis; LEAKAGE-FLUX; CORELESS; GENERATOR; COST; Engineering; Mechanics; Physics